Penerapan Aplikasi Sistem Pakar Untuk Mendiagnosa Penyakit Kucing Berbasis Web Menggunakan Metode Forward Chaining Dan Certainty Factor - Febrina Shanti Nurrachma; Nuril Lutvi Azizah; Metatia Intan Mauliana (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2023)
Cats are animals that are loved and admired by the public because of their beautiful physical shape and adorable behavior. But most cat keepers do not know how to treat and do not know the disease experienced by their pets just by looking at the symptoms of the disease that occurs in cats. So many cat owners are not aware if their cat has a disease and is late in providing treatment. From these problems, an expert system is needed that can help in solving problems, an expert system application that adopts artificial intelligence in the field of veterinary medicine that can diagnose diseases in cats. The purpose of this research is to build an expert system that is useful as a tool for diagnosing diseases in cats based on the web using forward chaining and certainty factor methods. This system is built using PHP and MySQL programming languages and based on the results of system functional testing using black box testing which states that the system is running well and all components produce the expected results and are able to assist users in diagnosing cat diseases, the results of disease diagnosis and the confidence value is in accordance between manual calculations and calculations on the system by bringing up the results of certainty value calculations  factor in each possible disease detected on the website. From the day of diagnostic testing, it was concluded that 33% of cats were diagnosed with feline calciirus, 33% of cats were diagnosed with feline panleuopenia, 40% of cats were diagnosed with feline rhinotracheitis, 37% of cats were diagnosed with helmathiasis, 80% of cats were diagnosed with otitis, 36% of cats were diagnosed with ringworm, 68% of cats were diagnosed with scabies.